‘URF SEBAGAI METODE ISTINBATH HUKUM ISLAM (Pemikiran Hasbi Ash-Shiddieqy dengan Fiqh Indonesianya) - Emi Yasir; Shafwan Bendadeh (STIS Nahdlatul Ulama Aceh, 2021)
Tengku Muhammad Hasbi Ash-Shiddieqy is one of the most influential scholars in Islamic law reform in Indonesia, he brings local traditions ('urf/'adat) as the construction of Islamic Indonesian characteristic law. According to Hasbi 'urf is the law which is alive in the community and could be fluctuated continuously and it could be a strong consideration for Islamic law implementation. Hasbi, in his scientifical oration entitled “Syariat Islam Menjawab Tantangan Zaman